Beyond ad hominem attacks: A typology of the discursive tactics used when objecting to news commentary on social media. - Ashley L Shea; Aspen K B Omapang; Ji Yong Cho; Miryam Y Ginsparg; Natalie N Bazarova; Winice Hui; René F Kizilcec; Chau Tong; Drew B Margolin (PLoS ONE)
Social media platforms increasingly serve as the primary place where people participate in public conversations about news. In these conversations, ad hominem attacks are quite common. Such ad hominem attacks might be influenced by underlying cognitive or affective goals, such as to discredit a purveyor of falsified evidence or to signal social distance from a hateful provocateur. They may also be driven by a simple operative goal: to stop what was said. When ad hominem attacks are used to stop the comments of another person, we refer to it as a discursive objection tactic. In this paper, we explore the prevalence of ad hominem attacks and characteristics of other discursive tactics used by people when objecting to online news commentary. First, we conducted a content analysis of more than 6,500 comment replies to trending news videos on YouTube and Twitter and identified seven distinct discursive objection tactics. Second, we examined the frequency of each tactic's occurrence from the 6,500 comment replies, as well as from a second sample of 2,004 replies. Our findings confirm that while ad hominem attacks are the most common discursive tactic used to object to news commentary, people also deploy a diversity of other discursive objection tactics. The resulting typology offers a comprehensive account of grassroots efforts which utilize deterrent speech, nonaccommodative communication and prosocial strategies.